The sponge-dwelling snapping shrimps (Crustacea, Decapoda, Alpheidae, Synalpheus) of Discovery Bay, Jamaica, with descriptions of four new species - Macdonald Iii, Kenneth S; Hultgren, Kristin; Duffy, J. Emmett (Zootaxa, 2009)
Twenty-two species of sponge-dwelling shrimp in the genus Synalpheus were collected in the vicinity of Discovery Bay, Jamaica. Four of these species are new to science. Synalpheus thele n. sp., S. corallinus n. sp., and S. plumosetosus n. sp. belong to a group of morphologically similar species that also includes S. brooksi, S. bousfieldi, S. carpenteri, and S. chacei. Synalpheus irie n. sp. is a highly distinctive shrimp most similar to S. mcclendoni, but can be distinguished from the latter by the unique bowl-shaped fingers of the major chela and the two-pronged distal protuberance on the palm of the major chela. Synalpheus belizensis and S. regalis are reported for the first time from outside their type localities in Belize, while S. bocas and S. duffyi are reported for the first time outside their type localities in Caribbean Panama.